What are the effects of edoxaban in the general population and in the elderly?. (22nd December 2016) - Verheugt, Freek W.A.
Abstract : Stroke and systemic embolism are common complications in patients with atrial fibrillation, and can be effectively prevented with oral anticoagulation. However, this strategy is associated with increased risk of major, sometimes fatal bleeding. Where vitamin K antagonists (VKAs) have been the standard of care in the past half century, new directly acting oral anticoagulants have been developed that, unlike VKA, have a fast onset and fast offset of action, and do not need monitoring either. These non-VKA oral anticoagulants (NOACs) have proven to be non-inferior to VKA with regards to stroke and systemic embolism and are at the same time also safer, especially where it is intracranial bleeding is concerned. Of the four registered NOACs, there is dabigatran as a direct inhibitor of thrombin, and three direct inhibitors of activated factor X: rivaroxaban, apixaban, and edoxaban. This survey deals with the latter NOAC in general and in the elderly in particular.